IMPLEMENTATION OF VILLAGE INFORMATION SYSTEM (SID) IN IMPROVING SERVICES TO THE COMMUNITY IN NORTH MILANGODAA VILLAGE, TOMINI DISTRICT, SOUTH BOLAANG MONGONDOW REGENCY - Yuyan Daaliwa; William Indra S Mooduto; Karlina Napu; Tri Setiawati Maulana (Governance: Jurnal Ilmu Administrasi Publik, 2024)
This study aims to evaluate the implementation of the Village Information System (SID) as a strategic effort to digitize village documents. The primary objective of this system is to transition traditional paper-based administration into a secure digital format, thereby enhancing data management and accessibility within the village office. The research follows a qualitative descriptive methodology. Data collection was conducted through field observations, in-depth interviews, and documentation studies. This approach allows for a comprehensive understanding of the system's integration into daily administrative routines. The findings indicate that the Village Information System (SID) significantly improves public service delivery in North Milangodaa Village, Tomini District, South Bolaang Mongondow Regency. As a specialized application, SID assists the village government in documenting and managing administrative data more efficiently, which ultimately facilitates a more streamlined public service process and faster data retrieval.